KEEFEKTIFAN MODEL GI TERHADAP KEMAMPUAN BERBICARA DI DEPAN KELAS IV SD - Tika, Anis Rahma; Wahyu, Ratna; Adhi, Singgih (JURNAL SINEKTIK, 2020)
The low ability to speak in front of the class has implications for the ability of students to convey their ideas directly. The effort to improve is by increasing the Group Investigation (GI) learning model. This research is a quantitative study with a pre-experimental one-group pretest-posttest design. The subjects used in this study were all fourth grade students of SD N Wonosoco Kudus which numbered 18 by using a nonprobability sampling technique with a type of saturated sampling. The technique of collecting data uses tests, interviews, observation and documentation. The results showed that the posttest average analytical thinking ability was higher at 86.78 compared to the pretest of 49.1. This is evidenced by the results of the t-test where the number of tcount (26,04)> ttable (2,032). So the results of speaking skills in front of the class have increased.